2019
DOI: 10.17816/kmj2019-147
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological picture of diabetic nephropathy in experimental diabetes mellitus

Abstract: Aim. To conduct a morphological study of the renal glomerulus in experimental diabetes mellitus and to study the pathomorphological features of the development of diabetic nephropathy. Methods. The study was carried out on 25 male Wistar rats. Modeling of diabetes mellitus was carried out by intraperitoneal injection of streptozotocin at a dose of 65 mg/kg. For more selective modeling of type 2 diabetes, the rats of the control group were intraperitoneally administered a solution of cytoflavin, calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…While the capillary rarefaction would decrease supplement of blood and oxygen, this leads to the loss of tubular cell viability, interstitial and glomerulosclerosis fibrosis ( Afsar et al, 2018 ). Recently, Filinova et al (2019) studied the pathomorphological features of STZ-induced diabetic mice model in the development of DN by using morphometrics method. Their findings revealed that the diabetic kidney is characterized by increased glomerular volume and significant glomerular capillary hyperemia.…”
Section: Abnormal Angiogenesis and Dnmentioning
confidence: 99%
See 1 more Smart Citation
“…While the capillary rarefaction would decrease supplement of blood and oxygen, this leads to the loss of tubular cell viability, interstitial and glomerulosclerosis fibrosis ( Afsar et al, 2018 ). Recently, Filinova et al (2019) studied the pathomorphological features of STZ-induced diabetic mice model in the development of DN by using morphometrics method. Their findings revealed that the diabetic kidney is characterized by increased glomerular volume and significant glomerular capillary hyperemia.…”
Section: Abnormal Angiogenesis and Dnmentioning
confidence: 99%
“…Moreover, the increased mesangial cell proliferation and thickened capillary basement membrane were observed as well. Finally, the urinary albumin excretion increased by 1.6 times ( Filinova et al, 2019 ). Moreover, the observed results supported the fact that there exists abnormal angiogenesis in glomeruli of DN mice model, which is in accordance with previous study ( Osterby and Nyberg, 1987 ).…”
Section: Abnormal Angiogenesis and Dnmentioning
confidence: 99%
“…Доза эплеренона была выбрана по результатам предыдущих исследований нефропротекторного действия препарата при модели СД [4]. В предварительных исследованиях нами показано, что типичные признаки нефропатии у крыс развиваются только к исходу 4-й нед после введения стрептозотоцина [6].…”
Section: материалы и методыunclassified
“…Earlier, having conducted a study, we described the biochemical and pathological picture of DN on the background of experimental streptozotocin (STZ)-induced DM in rats for a period of 1 month. (7,8) The outcome of the 1-month STZ-induced DM was that hyperglucosuria and proteinuria developed, that FRO process was activated and that a number of characteristic morphological signs of glomerulus damage had emerged. (7,8) However, it is widely believed that persistent nephropathy develops only after 8 months of DM modeling.…”
Section: Introductionmentioning
confidence: 99%
“…(7,8) The outcome of the 1-month STZ-induced DM was that hyperglucosuria and proteinuria developed, that FRO process was activated and that a number of characteristic morphological signs of glomerulus damage had emerged. (7,8) However, it is widely believed that persistent nephropathy develops only after 8 months of DM modeling. In this regard, the research objective was to investigate the pathological picture of DN in the 8-month STZ-induced DM and compare it with the previously obtained picture of DN in the 1-month STZ-induced DM.…”
Section: Introductionmentioning
confidence: 99%